The Difference between the Use of the Word Influence and Correlation in Quantitative Research and Its Implications - M. I. Suhifatullah; Mastur Thoyib (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Logical and rational ways of thinking are the main characteristics of scientific thought, apart from being systematic, measurable, and factual. But in fact, many scientific works such as theses and lecturers' research that use the words influence and correlation both use a correlational approach in their methodology or there is no difference. This is a denial of logical and rational thought, even though it may go unnoticed out of ignorance. This paper is expected to provide a correct understanding of the differences in the use of the word influence and correlation in quantitative research and its implications for research methodology.